2020
DOI: 10.1002/jts.22635
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Effects of Life Threat, Killing Enemy Combatants, and Unjust War Events in U.S. Service Members

Abstract: Although previous studies have identified behavioral health risks associated with combat exposure, it is unclear which types of combat events are associated with these risks, particularly regarding contrasts among the risks associated with life‐threatening experiences, killing combatants, and exposure to unjust war events, such as killing a noncombatant or being unable to help civilian women and children. In the present study, we examined surveys from 402 soldiers following deployment (i.e., baseline) and agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…While results from other studies on killing a noncombatant consistently demonstrated an association with adverse health outcomes, findings for killing an enemy combatant were mixed [ 10 , 25 , 28 , 29 ]. In the present study, we found those who killed an enemy combatant were more likely to experience mental health disorders, consistent with results from at least one other study [ 25 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While results from other studies on killing a noncombatant consistently demonstrated an association with adverse health outcomes, findings for killing an enemy combatant were mixed [ 10 , 25 , 28 , 29 ]. In the present study, we found those who killed an enemy combatant were more likely to experience mental health disorders, consistent with results from at least one other study [ 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…Taken together, these findings support previous research suggesting that killing a noncombatant is particularly associated with poorer health outcomes compared with killing an enemy combatant [ 10 , 25 , 27 , 28 ]. Being directly responsible for the death of a noncombatant may go against the service member’s moral code [ 17 , 29 , 52 ], whereas killing an enemy combatant may eliminate a potential threat, serve as a marker of operational success, and be regarded as consistent with the warrior ethos [ 29 ]. Events that challenge the moral and ethical foundation of service members can influence all aspects of their lives, contributing to mental and physical health problems [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with those of a study of 400 soldiers that found that unjust war events (but not killing enemy combatants) were associated with adverse mental health outcomes. 31 However, operationalization differences may at least partially explain the discrepancies. Specifically, in that study, “unjust war events” included being responsible for noncombatant deaths (as well as witnessing brutality toward noncombatants, ill or injured women or children, and Geneva Convention violations), and “killing enemy combatants” included an item that can be categorized as a fighting variable (“shooting/directing fire at enemy”).…”
Section: Discussionmentioning
confidence: 99%
“…Being responsible for the death of others during combat has also been associated with STBs, demonstrating large effect sizes compared with other types of combat experiences. 17,18,28,30 However, whether these findings extend to active-duty soldiers in the post-September 11, 2001 era, [31][32][33] a group whose suicide rates have increased substantially over the past decade, remains relatively unexplored. 34,35 In the current study, we examined the association between responsibility for the death of others in combat and postdeployment mental health outcomes (eg, PTSD, major depressive episode [MDE], STBs, and functional impairment) among active-duty US Army personnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation